2016
DOI: 10.1177/1362361315607724
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis lost: Differences between children who had and who currently have an autism spectrum disorder diagnosis

Abstract: Autism spectrum disorder (ASD) diagnoses sometimes change due to misdiagnosis, maturation, or treatment. This study uses a probability-based national survey—the Survey of Pathways to Diagnosis and Services—to compare currently diagnosed (n=1420) and previously diagnosed (n=187) children aged 6–17 years based on retrospective parental reports of early concerns about their children’s development, responses to those concerns by doctors and other health care providers, the type of provider who made the first ASD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 44 publications
0
28
0
5
Order By: Relevance
“…Fein et al (2013) reported that good or optimal outcomes for ASD ranged widely, from about 1 % to nearly 50 %. Blumberg et al (2015) reported that 13 % of 1607 individuals diagnosed with ASD in childhood no longer met criteria for ASD: 9 % had been initially misdiagnosed and 4 % Blostt heir ASD due to treatment or maturation. Helles et al (2015) found that 24 % of individuals diagnosed initially with Asperger's disorder no longer met criteria for any developmental disorder.…”
Section: Predictors Of Asd Outcome Are Variedmentioning
confidence: 99%
“…Fein et al (2013) reported that good or optimal outcomes for ASD ranged widely, from about 1 % to nearly 50 %. Blumberg et al (2015) reported that 13 % of 1607 individuals diagnosed with ASD in childhood no longer met criteria for ASD: 9 % had been initially misdiagnosed and 4 % Blostt heir ASD due to treatment or maturation. Helles et al (2015) found that 24 % of individuals diagnosed initially with Asperger's disorder no longer met criteria for any developmental disorder.…”
Section: Predictors Of Asd Outcome Are Variedmentioning
confidence: 99%
“…Each child is likely to have individual clusters of comorbid challenges. Furthermore, assessment at one point in time is unable to address the uncertainty that arises due to changes over time, which may move children into, or out of, diagnostic categorisation . In response to this uncertainty, diagnostic methodologies vary considerably .…”
Section: Nbp Services and Clinical Uncertaintymentioning
confidence: 99%
“…Furthermore, assessment at one point in time is unable to address the uncertainty that arises due to changes over time, which may move children into, or out of, diagnostic categorisation. [9][10][11] In response to this uncertainty, diagnostic methodologies vary considerably. 12 They may be influenced further by non-clinical factors, such as the opportunities for intervention funding.…”
mentioning
confidence: 99%
“…A final source of within‐diagnosis heterogeneity is the imprecision that arises at diagnostic boundaries, when arbitrary cut‐off points are used to define dichotomous diagnoses within spectrum conditions. As a result, children whose clinical presentation falls near these boundaries may move into, or out of, diagnostic categories over time …”
Section: Uncertainty In Diagnosismentioning
confidence: 99%
“…As a result, children whose clinical presentation falls near these boundaries may move into, or out of, diagnostic categories over time. 6 In addition to the variation due to diagnostic type and withindiagnosis heterogeneity, further complexity arises from individual patterns of comorbid problems. Comorbid problems are common in NBP practice.…”
Section: Uncertainty In Diagnosismentioning
confidence: 99%